Working in mental health : practice and policy in a changing environment - Phillips, Peter, 1968-; Sandford, Tom; Johnston, Claire, MSc RGN (New York : Routledge, 2012)
'A paradigm shift in the ways in which mental health services are delivered is happening - both for service users, and for professional mental healthcare workers. A more influential service user movement, a range of new community-based mental healthcare programmes delivered by an increasing plurality of providers and new mental health policy and legislation are all changing the landscape. Written by a team of experienced authors, and drawing on their expertise in policy, clinical leadership as well as user perspectives, this textbook explains how mental health services and their staff can operate and contribute in this new environment. Divided into three parts, the first focuses on the socio-political environment, incorporating service user perspectives. Part two goes on to look at current themes and ways of working in mental health - including chapters on recovery, the IAPT programme and mental healthcare for specific vulnerable populations. The final part explores new and future challenges, such as changing professional roles and commissioning services. The book focuses throughout on the importance of public health approaches to mental healthcare. This important text will be of interest to all those studying and working in mental healthcare, whether from a nursing, medical, social work or allied health background'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Mental health services -- United Kingdom; Mental health policy -- United Kingdom